A DFT and molecular docking study of xerantholide and its interaction with Neisseria gonorrhoeae carbonic anhydrase. (December 2022) - Nyambe, Moola M.; Archibong, Edet F.; Chinsembu, Kazhila C.
Abstract: Xerantholide is a sesquiterpene lactone that has anti-gonorrhea and anti-plasmodium activities. We present gas-phase electronic structure calculations of the equilibrium geometry of xerantholide, its adiabatic electron affinity (AEA), adiabatic ionization energy (AIE) and the energy barrier ( Δ E ‡ ) connecting the lowest energy conformers of the sesquiterpene. The computations were performed with the B3LYP, M06-2X and ωB97xd variants of the density functional theory (DFT) in conjunction with large basis sets. With the inclusion of the vibrational zero point energy, the computed AEA range from 0.740 eV [B3LYP/Aug-CC-pVTZ] to 0.774 eV [B3LYP/6-311++G(d, p)], and the AIE is roughly 8.6 eV at all theoretical levels. At the B3LYP/Aug-CC-pVTZ level, the barrier ( Δ E ‡ ) connecting the two lowest energy conformers is predicted to be 13.9 kcal/mol. Based on the molecular docking analysis, xerantholide interacts with the active site of Neisseria gonorrhoeae carbonic anhydrase (NgCA) via hydrogen bonding, metal-acceptor interaction, and non-polar alkyl and pi-alkyl interactions. The predicted binding affinity of − 6.8 kcal/mol compares well with those obtained for standard NgCA inhibitors such as acetazolamide (−5.7 kcal/mol). A biomimetic model study involving xerantholide and zinc-tris imidazole ([ZnIm3 ] 2+ ) ion was also carried out at different theoretical levels to estimate the interaction energy for the formation of the complex formed between the ligand and the active site model of NgCA. The binding free energy (ΔG) has been calculated to be − 28.5 kcal/mol at the B3LYP/6-311++G(d, p) level. The interaction mode observed in both the docking and the model calculations involves the lactone ring. Graphical Abstract: ga1 Highlights: Xerantholide has two dominant conformers with electronic energy difference of about 4.0 kcal/mol. Electronic properties indicate that xerantholide is a soft molecule. Xerantholide has high binding affinity to Neisseria gonorrhoeae carbonic anhydrase comparable to acetazolamide a known carbonic anhydrase inhibitor. DFT methods that include dispersion corrections (DFT-D2, M062x and w97xd) are suitable for this system.